Porte de armas. - RODRIGUES, Carlos Eduardo Marangoni; ASSUNÇÃO, João Mateus Dias (138, 2018)
O porte de armas pode ser um risco para algumas pessoas da população brasileira, já para outras, pode ser um benefício, pois, para elas é um jeito de se defender de indivíduos que praticam atos ilícitos ou atos que as ameaçam. Foi explicado que a arma foi criada na China, no século IX, sendo elas consideradas rústicas e artesanais. Sendo assim, o Brasil contém o Estatuto do Desarmamento, não podendo liberar o porte para qualquer brasileiro, somente para aqueles que seguirem os requisitos que são pedidos pela lei. Assim, pudemos comparar o Brasil com outros países que contêm ou não o porte de armas liberado. Após o conhecimento alcançado, falou-se sobre os pontos negativos e positivos que o porte de armas pode trazer. Foi-se a campo para saber o que a população acha sobre o porte de armas no Brasil.

The coat of arms, in the context of the release of arms, it may be a risk for some people in the Brazilian population. For other people, it may be a benefit because it is a way of defending others who commit illicit acts or acts that threaten them. Thus explaining that the weapon was created in China in the ninth century, being considered rustic and handcrafted. Therefore, Brazil contains the Disarmament Statute, not being able to release the size for each of the Brazilian population, only for those who follow the requirements that are requested in it. Thus we can compare Brazil with other countries that contain or do not contain the release of arms released, whether it is necessary or not necessary in some countries. And after the knowledge given to you, we will talk about the negative and positive points that the bearing of arms can have when carrying it. For we went to the field to know what the population thinks if the possession of arms was released in Brazil.
Carrying weapons.
Keywords: Morte; Porte de arma; Desarmamento; Estatuto; População - Brasil; Gestão e Negócios